2021
DOI: 10.1002/jmv.27459
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of SARS‐CoV‐2 antigen test sample as input for SARS‐CoV‐2 RT‐PCR analysis

Abstract: SARS‐CoV‐2 rapid detection is of great interest to prevent viral dissemination. In that sense, antigen tests appeared as a very valuable tool to reach this goal. However, it is possible to obtain a negative result in those patients with low viral loads, and consequently, reverse transcription‐polymerase chain reaction (RT‐PCR) should be performed on samples from patients with a negative antigen test in which there is a strong suspicion of COVID infection. The common diagnostic algorithm involves taking a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several studies have shown a wide range of sensitivities associated with SARS-CoV-2 RADTs which is very dependent upon the viral load. Sensitivity can range from 95%, when a high concentration of viral capsid antigens are present in the sample, to 10–30% when the viral load is low ( 6 , 7 ). In most clinical cases, SARS-CoV-2 RADT results needed to be confirmed by qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a wide range of sensitivities associated with SARS-CoV-2 RADTs which is very dependent upon the viral load. Sensitivity can range from 95%, when a high concentration of viral capsid antigens are present in the sample, to 10–30% when the viral load is low ( 6 , 7 ). In most clinical cases, SARS-CoV-2 RADT results needed to be confirmed by qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide availability of diagnostic tests, the sensitivity is related to the cycle threshold (Ct) value regardless of vaccine status and/or symptoms. All negative results must be verified using molecular assay [ 11 ].…”
Section: New Advances In Microbiological Diagnosis Of Sars-cov-2 Infe...mentioning
confidence: 99%
“…The disease can be detected soon after the first days of symptoms appear, not requiring a complex laboratory structure. However, these tests offer lower sensitivity and specificity when compared to RT-PCR and, sometimes, they must be repeated [ 9 ]. On the other hand, RT-PCR has better accuracy, even in the first days of infection, even before the onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, RT-PCR has better accuracy, even in the first days of infection, even before the onset of symptoms. As disadvantages, these tests have a higher cost, require a more complex laboratory structure and longer time to process the results [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%